Islamic & Conventional Mutual Funds Performance by Return and Risk Adjusted Performance - Elmanizar, Elmanizar; Aveliasari, Erythrina (SEKOLAH TINGGI EKONOMI ISLAM SEBI, 2023)
This study compares the performance of Islamic and conventional mutual funds from 2017 to 2021 with the aim of analyzing the differences. This study makes use of secondary data from the Otoritas Jasa Keuangan (OJK) for 5 years that were downloaded from the OJK's official website (OJK). Purposive sampling is used in this study sampling method. The Mann-Whitney U Test is the analysis technique employed. According to the study's findings, there are no appreciable differences between mutual fund risk and market risk for Islamic mutual funds in terms of beta, return, and Sharpe. While there are variances between the Treynor, Jensen Alpha, M2 Measurement, and Appraisal Ratio techniques. Penelitian ini membandingkan kinerja reksa dana syariah dan konvensional dari tahun 2017 sampai dengan 2021 dengan tujuan untuk menganalisis perbedaannya. Penelitian ini memanfaatkan data sekunder dari Otoritas Jasa Keuangan (OJK) selama 5 tahun yang diunduh dari website resmi OJK. Purposive sampling digunakan dalam metode pengambilan sampel penelitian ini. Mann-Whitney U Test adalah teknik analisis yang digunakan. Menurut temuan penelitian, tidak ada perbedaan yang cukup berarti antara risiko reksa dana dan risiko pasar untuk reksa dana syariah dalam hal beta, return, dan Sharpe. Sedangkan terdapat perbedaan yang bervariasi antara teknik Treynor, Jensen Alpha, M2 Measurement, dan Appraisal Ratio.